2005
DOI: 10.1111/j.1742-4658.2005.04794.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro selection and characterization of a stable subdomain of phosphoribosylanthranilate isomerase

Abstract: The (βα)8‐barrel is the most common enzyme fold and it is capable of catalyzing an enormous diversity of reactions. It follows that this scaffold should be an ideal starting point for engineering novel enzymes by directed evolution. However, experiments to date have utilized in vivo screens or selections and the compatibility of (βα)8‐barrels with in vitro selection methods remains largely untested. We have investigated plasmid display as a suitable in vitro format by engineering a variant of phosphoribosylant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Previously, this sequence was subcloned with an initiator methionine, a C-terminal His 6 tag and a threeresidue linker (Ala-Gly-Ser) between trPRAI and the His 6 tag. 25 We expressed this C-terminally His 6 -tagged version of trPRAI in E. coli and purified the recombinant protein using nickel affinity and sizeexclusion chromatography (SEC). The symmetrical gel-filtration profile of trPRAI at two concentrations indicates a monodisperse species, and multi-angle laser light-scattering (MALLS) data show that the protein is monomeric in solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, this sequence was subcloned with an initiator methionine, a C-terminal His 6 tag and a threeresidue linker (Ala-Gly-Ser) between trPRAI and the His 6 tag. 25 We expressed this C-terminally His 6 -tagged version of trPRAI in E. coli and purified the recombinant protein using nickel affinity and sizeexclusion chromatography (SEC). The symmetrical gel-filtration profile of trPRAI at two concentrations indicates a monodisperse species, and multi-angle laser light-scattering (MALLS) data show that the protein is monomeric in solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…25 Unlike other part-barrel subdomains, trPRAI is readily purified from the soluble cell lysate. Here, we report that trPRAI is monomeric and well ordered in solution, and our NMR-derived solution structure of trPRAI demonstrates unequivocally that three-quarter barrels can indeed form native-like structures in solution.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of pMS401, for the expression of (His) 6 -tagged E. coli PRAI, was described previously. 55 The E. coli trpC gene, encoding residues 1-259 of the bifunctional IGPS:PRAI monomer, 21 was amplified from the ASKA clone pCA24N-trpCF using primers trpC_NcoI.for and trpC_BamHI.rev. These oligonucleotides also encoded restriction sites, enabling the digestion of the PCR product with NcoI and BamHI and its ligation with pMS401 (which had been treated with the same enzymes to excise trpF).…”
Section: Cloning Trp Genesmentioning
confidence: 99%
“…Previously, it has been shown that selections with the PD system could be performed in the Escherichia coli cytoplasmic milieu without purification. 21,24 It was not clear if the contaminating prokaryotic material would adversely affect the transfection of mammalian cells.…”
Section: Resultsmentioning
confidence: 99%